2019
DOI: 10.1016/j.annemergmed.2019.08.256
|View full text |Cite
|
Sign up to set email alerts
|

298 Characteristics and Utilization Patterns of Homeless and Housing-Insecure Patients Presenting to Emergency Departments Across a Large Health System

Abstract: Conclusion: Nurse participation in ED HCV screening within a single practice environment varies highly between individuals. This challenges the assertion that insufficient resources, including provider time, are the primary reason that ED providers cannot participate in screening programs. Improved understanding of individual provider-level reasons for non-participation is essential to optimize implementation of screening and prevention programs in EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, housing instability was operationalized using 5 ICD-10 Z-Codes addressing aspects of the housing instability continuum, including but not exclusive to homelessness: homelessness (Z59.0); inadequate housing (Z59.1); discord with neighbors, lodgers, and landlords (Z59.2); problems related to living in a residential institution (Z59.3); and other problems relating to housing and economic circumstances (Z59.8: housing instability, housed: with risk of homelessness; homelessness in past 12 months, unspecified; other problems related to housing and economic circumstances; and problem related to housing and economic circumstances, unspecified). Consistent with other work, this study reviewed and identified coded housing instability for hospitalizations with at least 1 of the 5 housing-related Z59-codes in the first 15 ICD-10 codes in the NIS data set. Patient-level characteristics included age (continuous variable), sex, race and ethnicity (Asian, Black, Hispanic, American Indian, White, and other, including multiple races and state-reported race categories excluded from other NIS categories), insurance type (Medicare, Medicaid, private, uninsured, other), elective or emergency admittance, major operating room procedure, and discharge type (routine transfer to short term hospital, other transfer, home health care, against medical advice).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, housing instability was operationalized using 5 ICD-10 Z-Codes addressing aspects of the housing instability continuum, including but not exclusive to homelessness: homelessness (Z59.0); inadequate housing (Z59.1); discord with neighbors, lodgers, and landlords (Z59.2); problems related to living in a residential institution (Z59.3); and other problems relating to housing and economic circumstances (Z59.8: housing instability, housed: with risk of homelessness; homelessness in past 12 months, unspecified; other problems related to housing and economic circumstances; and problem related to housing and economic circumstances, unspecified). Consistent with other work, this study reviewed and identified coded housing instability for hospitalizations with at least 1 of the 5 housing-related Z59-codes in the first 15 ICD-10 codes in the NIS data set. Patient-level characteristics included age (continuous variable), sex, race and ethnicity (Asian, Black, Hispanic, American Indian, White, and other, including multiple races and state-reported race categories excluded from other NIS categories), insurance type (Medicare, Medicaid, private, uninsured, other), elective or emergency admittance, major operating room procedure, and discharge type (routine transfer to short term hospital, other transfer, home health care, against medical advice).…”
Section: Methodsmentioning
confidence: 99%